A New Typification Method for Combined Linear Building Patterns with the Resolution of Spatial Conflicts - Ying Tong; Qingsheng Guo; Wei Zhu; Chuanbang Zheng (ISPRS International Journal of Geo-Information)
Typification is a crucial generalization operator for maintaining the structure of building patterns in map generalization. However, in densely built-up areas, the structure of building patterns is complicated, and spatial conflicts exist not only within building patterns but also between them. Applying typification solely to individual patterns fails to resolve conflicts between them and does not adequately preserve their spatial distribution. To address these challenges, this study proposes a new typification method that treats linear building patterns with common buildings as a whole named combined linear patterns, simultaneously resolving the spatial conflict both within and between combined linear patterns. Firstly, linear building patterns and combined linear patterns are recognized, respectively, using visual perception principles and the common elements of linear building patterns. Secondly, spatial conflicts within the combined linear pattern are resolved through the segmental building reconstruction of linear building patterns and a reduction in linear building patterns at junction buildings. Finally, spatial conflicts between combined linear patterns are solved based on the position and number of conflict buildings in the patterns. The proposed method is evaluated using a building dataset from OpenStreetMap. The experimental results indicate that the proposed method can preserve the spatial distribution of building patterns with better legibility than the usual typification method for individual linear building patterns.